Enzyme and AIEgens Modulated Solid‐State Nanochannels: In Situ and Noninvasive Monitoring of H2O2 Released from Living Cells. Issue 2 (15th November 2019) - Lou, Xiaoding; Song, Yongjun; Liu, Rui; Cheng, Yong; Dai, Jun; Chen, Qing; Gao, Pengcheng; Zhao, Zujin; Xia, Fan
Abstract: Solid‐state nanochannels have revealed great abilities in the sensing of ions, small biomolecules, and biological macromolecules. However, the current platform requires pretreatment of real samples to extract targets, which may induce false signals due to complicated collection and addition processes. Although nanopore electrodes or nanopipettes have been successfully utilized in the detection of intracellular redox‐active species without sample preparation processes, the insertion of nanoprobes to living cells is inevitable. Here, a strategy is reported to monitor H2 O2 released from living cells based on functionalized solid‐state nanochannels without an insertion procedure. In this strategy, aggregation‐induced emission luminogens (AIEgens) with enzyme‐responsive linkage properties are combined in solid‐state nanochannels. When H2 O2 released from cervical cancer cells (HeLa), Tyr‐containing AIEgens (TT) will form horseradish peroxidase‐modulated (HRP‐modulated) linkages in the nanochannels. The formation of linkages can result in the effective blockade of nanochannels, hence via transmembrane ionic current. Owing to the aggregation of linkage products, a fluorescence signal can be observed. By using these dual‐signal‐output nanochannels, in situ and noninvasive detection of H2 O2 is able to be achieved. Together with molecular dynamic (MD) simulations results, solid surface zeta potential and contact angle experiments, it is concluded that the blockage of nanochannels is the dominate factor for ionic currents as well as fluorescence change. Abstract : Living cells are first incubated on a flexible polyethylene terephthalate (PET) membrane and then inserted into the left chamber of a nanochannels device. When H2 O2 is released from living cells, a Tyr‐containing tetraphenylethylene (TPE) derivative (TT) forms horseradish peroxidase (HRP)‐modulated linkage in the nanochannels, which is covalently attached to capture probes. By using this dual‐signal‐output (ionic current and fluorescence) nanochannel device, in situ and noninvasive detection of H2 O2 can be achieved.